A flagellum-specific chaperone facilitates assembly of the core type III export apparatus of the bacterial flagellum. - Florian D Fabiani; Thibaud T Renault; Britta Peters; Tobias Dietsche; Eric J C Gálvez; Alina Guse; Karen Freier; Emmanuelle Charpentier; Till Strowig; Mirita Franz-Wachtel; Boris Macek; Samuel Wagner; et al. (PLoS Biology)
Many bacteria move using a complex, self-assembling nanomachine, the bacterial flagellum. Biosynthesis of the flagellum depends on a flagellar-specific type III secretion system (T3SS), a protein export machine homologous to the export machinery of the virulence-associated injectisome. Six cytoplasmic (FliH/I/J/G/M/N) and seven integral-membrane proteins (FlhA/B FliF/O/P/Q/R) form the flagellar basal body and are involved in the transport of flagellar building blocks across the inner membrane in a proton motive force-dependent manner. However, how the large, multi-component transmembrane export gate complex assembles in a coordinated manner remains enigmatic. Specific for most flagellar T3SSs is the presence of FliO, a small bitopic membrane protein with a large cytoplasmic domain. The function of FliO is unknown, but homologs of FliO are found in >80% of all flagellated bacteria. Here, we demonstrate that FliO protects FliP from proteolytic degradation and promotes the formation of a stable FliP-FliR complex required for the assembly of a functional core export apparatus. We further reveal the subcellular localization of FliO by super-resolution microscopy and show that FliO is not part of the assembled flagellar basal body. In summary, our results suggest that FliO functions as a novel, flagellar T3SS-specific chaperone, which facilitates quality control and productive assembly of the core T3SS export machinery.